Stability of regime-switching processes under perturbation of transition rate matrices. (August 2019) - Shao, Jinghai; Yuan, Chenggui
Abstract: This work is concerned with the stability of regime-switching processes under the perturbation of the transition rate matrices From the viewpoint of application, two kinds of perturbations are studied: the size of the transition rate matrix is fixed, and only the values of entries are perturbed; the values of entries and the size of the transition matrix are all perturbed. Moreover, both regular and irregular coefficients of the underlying system are investigated, which clarifies the impact of the regularity of the coefficients on the stability of the underlying system.